Innovation and Industry 4.0 in building the international competitiveness of food industry enterprises: The perspective of food industry representatives in Poland - Łukiewska, Katarzyna (Economics and Business Review, 2024)
The aim of the research is to determine the impact of innovations and Industry 4.0 solutions on the international competitiveness from the perspectives of representatives of food industry enterprises. The empirical layer used information collected on the basis of a survey using the CATI method conducted on a representative sample of representatives of food industry enterprises. Descriptive statistics, the Kruskal-Wallis test, Mann-Whitney test, multiple comparison test and box-plot plots were used to analyse the data. The study confirmed that implementing certain innovations and solutions, both intangible and tangible, is important for maintaining and improving competitiveness on the international market. This applies particularly innovative, modern ways of reaching the customer, developing innovative products, the use of IT systems and the use of innovative methods in advertising and promotion. The conclusions present direct implications for managers of food enterprises who formulate competitive strategies.